The semidiurnal tide in the middle atmosphere of Mars. Issue 10 (31st May 2013) - Kleinböhl, Armin; John Wilson, R.; Kass, David; Schofield, John T.; McCleese, Daniel J.
Abstract: [1] Atmospheric thermal tides are global oscillations in atmospheric fields that are subharmonics of a solar day. While atmospheric tides on Earth are mainly relevant in the upper atmosphere, on Mars, they dominate temperature variations and winds throughout the atmosphere. Observations and model simulations to date have suggested that the migrating diurnal tide is the predominant mode in the Martian atmosphere, and that the semidiurnal tide is only relevant in the tropical middle atmosphere during conditions of high dust loading. New comprehensive observations by the Mars Climate Sounder in a geometry that allows coverage of multiple local times show that the semidiurnal tide is a dominant response of the Martian atmosphere throughout the Martian year. The maximum semidiurnal amplitude of ~ 16 K is found at southern winter high latitudes, which makes it the largest tidal amplitude observed in the Martian middle atmosphere outside of dust storm conditions. The semidiurnal tide can be successfully modeled due to recent advances of Mars General Circulation Models (MGCMs) that include the radiatively active treatment of water ice clouds. Tidal forcing occurs through absorption of radiation by aerosols and points to the vertical structure of dust and clouds and their radiative effects as being essential for our understanding of the thermal structure and the general circulation of the Martian atmosphere. As with terrestrial GCMs trying to quantify mechanisms affecting climate, future Mars modeling efforts will require microphysical schemes to control aerosol distributions, and vertically and temporally resolved measurements of temperature and aerosols will be essential for their validation. Key Points: MCS observes a strong semi‐diurnal tide in Mars' atmosphere at all seasons. Radiatively active water ice clouds provide tidal forcing. The vertical structure of aerosols is essential to model Mars' atmosphere.